2019
DOI: 10.1002/ppap.201800198
|View full text |Cite
|
Sign up to set email alerts
|

Microwave discharge in liquid n‐heptane with and without bubble flow of argon

Abstract: Emission spectra and gas products of microwave discharge in liquid n‐heptane with and without argon bubbling (6–40 l h−1) are investigated. The discharge was excited in a system with a coaxial input of energy. The pressure above the surface of the liquid was equal to atmospheric pressure. It is shown that the addition of argon changes the spectral composition of the plasma radiation, in which the emission of hydrogen and argon atomic lines appears. The addition of argon does not affect the rotational and vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Another method of microwave plasma generation in liquids is the coaxial input of microwave energy into the liquid, in which the discharge is ignited at the end of the central conductor of coaxial line (Figure 2c). It is the most widespread method of microwave plasma generation in liquids (see, e.g., [14,15,28,[37][38][39][40][41][42][43][44][45]). Modeling of electrodynamics of quarter wavelength [30] and coaxial [44] antenna systems has shown that in the latter system the microwave field strength at the tip of antenna is much less sensitive to the antenna length.…”
Section: Experimental Setups and Methods Of Diagnosticsmentioning
confidence: 99%
See 4 more Smart Citations
“…Another method of microwave plasma generation in liquids is the coaxial input of microwave energy into the liquid, in which the discharge is ignited at the end of the central conductor of coaxial line (Figure 2c). It is the most widespread method of microwave plasma generation in liquids (see, e.g., [14,15,28,[37][38][39][40][41][42][43][44][45]). Modeling of electrodynamics of quarter wavelength [30] and coaxial [44] antenna systems has shown that in the latter system the microwave field strength at the tip of antenna is much less sensitive to the antenna length.…”
Section: Experimental Setups and Methods Of Diagnosticsmentioning
confidence: 99%
“…The presented photographs reflect the non-stationary nature of microwave discharges in liquids. Gas products of microwave discharge in n-heptane are studied much better than in other hydrocarbons [43], and it is possible to compare these results with the results obtained in other conditions.…”
Section: Gas Products Of Microwave Discharges In Liquid Hydrocarbonsmentioning
confidence: 99%
See 3 more Smart Citations